The Improving Beginning Reading Skills Using Structural Analytic Synthetic (SAS) Methods in Elementary Schools - Suci Ika Rahmi; Yanti Yandri Kusuma; Iis Aprinawati (Edumaspul: Jurnal Pendidikan, 2022)
This study aims to determine the improvement of students' initial reading skills on the theme of me through the Synthetic Structural Analytical Method (SAS) in grade 1 of the State Elementary School 001 Pulau. This research is a classroom action research. The subjects of this research are teachers and students. Meanwhile, the object of this research is the Structural Analytical Synthetic (SAS) method and the students' initial reading skills. This research was carried out in 2 cycles, each cycle was carried out in 2 meetings. Data collection techniques used in this study were observation, tests and documentation. Based on the results of the study that before the action 2 students or 10% were in the complete category and 17 students or 89% were in the incomplete category. Then corrective action was taken using the Structural Analytic Synthetic (SAS) method. In the first cycle of students' initial reading skills there was an increase, 4 students or 22% were in the complete category and 14 students or 77% were in the incomplete category. In cycle II, the students' initial reading skills increased again to 16 students or 88% were in the complete category and only 2 students or 11% were in the incomplete category. Thus, it can be concluded that the Structural Analytical Synthetic (SAS) method can improve students' initial reading skills on the theme of me in grade 1 of the State Elementary School 001 Pulau. Keywords: Beginn